USE OF MODERN INNOVATIVE TECHNOLOGIES DURING THE LESSON - Uljalgas Tulegenqizi Abdullayeva (Journal Park Publishing, 2022)
This article talks about how to use modern innovative technologies during the lesson in advanced educational conditions. Methods of making education more effective, information about the importance of innovative educational technologies was also given.
Keywords: interactive methodology, innovative education, innovations, pedagogical technologies, information technologies